2011
DOI: 10.1007/s11356-011-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sampling sufficiency on biodiversity analysis of microperiphyton communities for marine bioassessment

Abstract: These results suggest that sampling sizes represented a significant influence on biodiversity analysis of microperiphyton communities for monitoring programs and ecological conservation researches in marine ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…. ., and 19-20 glass slides at two depths Many investigations have demonstrated that the observed species richness of a community along with functional parameters are strongly influenced by sampling effort, and that rarefaction processes cannot negate the influence of sampling effort on γ-diversity (e.g., Clarke et al 2011;Xu et al 2011Xu et al , 2012a. In this study, the rarefied average species richness and functional parameters were weakly sensitive to sampling influence, i.e.,~8 glass slides were sufficient to achieve coefficients of variation of <5 % in functional parameters based on the average species richness.…”
Section: Discussionmentioning
confidence: 51%
“…. ., and 19-20 glass slides at two depths Many investigations have demonstrated that the observed species richness of a community along with functional parameters are strongly influenced by sampling effort, and that rarefaction processes cannot negate the influence of sampling effort on γ-diversity (e.g., Clarke et al 2011;Xu et al 2011Xu et al , 2012a. In this study, the rarefied average species richness and functional parameters were weakly sensitive to sampling influence, i.e.,~8 glass slides were sufficient to achieve coefficients of variation of <5 % in functional parameters based on the average species richness.…”
Section: Discussionmentioning
confidence: 51%
“…Sample processing was conducted according to the methods described by Xu et al (2011Xu et al ( , 2012. Identifications were carried out following the references such as Song et al (2009) and Hasle and Syvertsen (1997).…”
Section: Dataset Collectionmentioning
confidence: 99%
“…Biofilm-dwelling microbial eukaryotes are the primary components of a biofilm or microperiphyton communities, and employ a vital role in the functioning of microbial food webs in aquatic ecosystems (Gold et al, 2002;Norf et al, 2009;Risse-Buhl and Küsel, 2009;Xu et al, 2012). Phototrophic microalgae (mainly benthic diatoms) devote the primary production (Xu et al, 2008;Debenest et al, 2009;Duong et al, 2010;Xu et al, 2012), whereas the heterotrophic protozoa act as variety of trophic-functional consumers, such as bacterivores, algivores, raptors and non-selectives, and transfer the flux of both elements and energy from picoand nano-plankton to benthos (Fischer et al, 2002;Kathol et al, 2009;Norf et al, 2009;Xu et al, 2011Xu et al, , 2014a.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations